Motivation of School Board Members to Support Equity and Social Justice in Public Education - (:unkn) unknown (My University, 2019)
This dissertation was designed to provide better access to current information on school board members’ desires to promote equity and social justice. Leaders are motivated to advance initiatives for various reasons including intrinsic, extrinsic, and other influencing factors. In this study, these factors are further researched focusing on school board members representing public school districts in southeastern Wisconsin that are founding members of the Closing the Achievement Gap Consortium and have served on a Board of Education that adopted school board policy specific to promoting equity in education. Through a qualitative descriptive design and the use of thematic analysis, the results of semi-structured interviews were analyzed to develop findings that contribute materially to the knowledge of what motivates school board members’ advocacy and leadership decisions. An analysis of the data revealed that educational equity and social justice in schools can be more readily attained by providing school board members with broad context and external perspectives on critical equity-related issues; a strong and aligned governance structure; activities and structures to engage in team-building exercises with the full board of education and superintendent; and opportunities to grow connections and boost relationships with others.